The suburbanisation of office development in Dublin and its transport implications - MacLaran, Andrew; Killen, James (Centre for Urban and Regional Studies. Trinity College Dublin, & the Faculty of the Built Environment, Dublin Institute of Technology. Bolton Street, 2002)
Cities exist primarily to accommodate the vast range offunctions associated with the division of labour. By and large, it is the private-sector property development sector which equips space to accommodate this multiplicity of operations. Competition for land and buildings between functions possessing different market power, together with the operation of planning systems which have historically favoured monofunctional zoning, have created an urban landscape in which functions tend to become geographically separated. Transport infrastructures provide the essential links between residential environments and employment locations. The first part of this paper reviews the changing location of office functions in Dublin in recent decades , its focus reflecting the growing significance of office-based employment in the urban economy. It reviews the shift in the geography of development from one which focused predominantly on the inner city during the 1960s until the 1980s, towards one in which numerous and widely-spread suburban sites accounted for a growing proportion of new development in the I 990s. The second part of the paper discusses some of the transport implications of these locational changes, paying particular attention to the potential role of public transport in catering for the resultant pattern of journeys to work. It alludes also to the extent to which the most important suburban office nodes will benefit if the currently proposed transport infrastructure developments (Dublin Transportation Office, 2000) are implemented. The implication for long-term land-use and transport planning policy are discussed at the end of the paper.
Keywords: Urban geography -- Ireland